Quantifying DNA-mediated liposome fusion kinetics with a fluidic trap. Issue 15 (31st March 2023) - Marie, Rodolphe; Rasmussen, Martin K.; Pedersen, Jonas N.
Abstract : DNA-induced liposome fusion kinetics measured in a nanofluidic trap follows second-order kinetics. Abstract : Self-assembly of synthetic lipid vesicles via lipid membrane fusion is a versatile tool for creating biomimetic nano- and micron-sized particles. These so-called liposomes are used in the development of biosensing platforms, design of drug delivery schemes, and for investigating protein-mediated fusion of biological membranes. This work demonstrates DNA-induced liposome fusion in a nanofluidic trap where the reaction occurs in a 15 femtoliter volume at homogeneous mixing. In contrast to current methods for fusion in bulk, we show that the fusion reaction follows second-order kinetics with a fusion rate of (170 ± 30)/(M −1 s −1 ) times the square number of DNA molecules per liposome. The nanofluidic trapping gives a full characterization of the size and charge of the liposomes before and after fusion. The chip-based approach limits the amount of sample (down to 440 vesicles) and can be parallelized for systematic studies in synthetic biology, diagnostics, and drug delivery.